Residents’ perceptions on impacts of hosting the “Guimarães 2012 European Capital of Culture”: comparisons of the pre-and post-2012 ECOC - Vareiro, Laurentina (2015)
The nomination of Guimarães, a small city located in the northwest of Portugal, as European capital of culture (ECOC) in 2012 raised great expectations in the local community towards its socio-economic and cultural benefits. As noted by various authors, namely Kim and Petrick (2005), Kim, Gursoy and Lee (2006) and Gursoy, Chi, Ai and Chen (2011), residents tend to have high expectations about the benefits of hosting a mega-event, although they tend to recognize that some costs will result from it. Therefore, the present research was designed to examine the Guimarães residents’ perceptions on the impacts of the 2012 European capital of culture (2012 ECOC) on the city and the municipality of Guimarães before and after the mega-event and the differences found between the two time periods.